A quantitative study on the adoption of facial recognition via smartphone in banking industry, a Malaysian perspective - Khoo, Yi Qi (2019)
The main objective of conducting this research project is to bring awareness to nationwide application for facial recognition by all banks in East and West Malaysia. Therefore, various factors were investigated such as perceived ease of use, perceived usefulness, awareness and security will bring impact on the adoption of facial recognition. Quantitative method approach are used and 350 survey questionnaires are distributed to Malaysian that comes from different states by using convenient sampling technique. Among 130 surveys are hardcopy while 220 surveys are softcopy. Through the use of Statistical Package for Social Science (SPSS), data that collected from the survey questionnaire are able to analyze. The results acquired from the SPSS shows that there is significant relationship between all independent variable towards the dependent variable. However, the variable awareness shown insignificant relationship towards the adoption of facial recognition. The research also mentioned about the limitations during the progress of research project and recommendation are provided for the future researchers.